Mirror game in the construction of Lope’s lyrical self. The case of sonnet “XVIII” of Rimas Sacras (1614) (Castilla. Estudios de Literatura, 2023)
Lope de Vega’s work is characterised by the use of autobiographical simulation, with a permanent game in which reality and fiction intertwine to give the reader the feeling of being faced with a true story. Starting from this premise, the purpose of this work is to unravel de configuration of Lope’s lyrical self, taking as reference the sacred book of poems of the Fénix, Rimas sacras (1614), and, above all, the sonnet “XVIII”. This poem, whose sources and influences are explored, serves as a characteristic example of the construction of a self that, without ceasing to be fictitious, plays at being a reflection of the real Lope.
Keywords: Lope de Vega; lyrical self; sonnet; Rimas sacras; Qué tengo yo que mi amistad procuras